Quality Evaluation Frameworks in Public Catering Services: Kerangka Kerja Evaluasi Kualitas dalam Layanan Katering Publik - Amalia, Annisa Alfi; Azizah , Nurul (Indonesian Journal on Health Science and Medicine, 2024)
This study examines quality assessment in public catering products using GOST R 50647-2010 standards, aiming to improve systematic evaluation methodologies. It introduces a classification system for quality indicators and focuses on cakes to quantify sensory attributes. Findings reveal a determining score of 41.5 based on taste, aroma, consistency, appearance, and shape, highlighting the effectiveness of structured assessment. The study emphasizes integrating comprehensive quality indicators, high-automation equipment, and skilled labor for quality assurance in public catering. It also discusses the association between anxiety levels, irregular menstrual cycles, and dysmenorrhea, proposing warm water compresses as a solution.